Organización administrativo-contable y análisis financiero a 216Expolllanta 2 de la ciudad de Loja, periodo enero-junio del 2015 - Castillo Gonzaga, Jenny Esperanza (2016)
The present thesis work entitled "accounting organization and analysis financial EXPOLLANTA 2 of the city of LOJA, period January-June of 2015", was developed according to their needs and characteristics, as well as in compliance with one of the requirements prior to choose the degree of engineer in accounting and auditing, counter Publico-auditor; his presentation is subject to General rules for ranking issued by the Universidad Nacional de Loja. In relation to the objectives of the thesis work, marked favorably. As specific, develop plan and same accounts manual to be used for the development of the accounting process within the company; compliance through the collection and verification of the documents took stands that were the basis for the accounting register to obtain financial statements that provide information of the resources are there, the results obtained, inflows and outflows which has resulted, among other financial aspects. The development of the thesis was based on the compilation of accountant information and financial analysis that allowed a proper development of activities based on legal provisions and various regulations that have been established for companies and organizations underway. The methodology that was used for the thesis work consisted of the collection of concepts and ideas such as: concepts and classifications of the records that are related to commercial accounting with the purpose of developing the accounting practice and to obtain results that allows its owner to make decisions in a timely and appropriate manner. Finally real, timely and reliable financial statements were obtained, and was made the financial analysis determined where the real situation of the 5 company, with the respective conclusions and recommendations focused to provide guidance to the owner in administrative aspects and control, which will tell with timely information for decision-making in the management of your company.